Study of LED Radiation Effects on Insect Phototaxis Response for the Development of Light-Based Pest Trap - Tay, Fei Siang; Chung , Wei Wee Bryan; Then , Yi Lung; Dyg, Norkhairunnisa Abang Zaidel; Kashem, Saad (International Journal of Integrated Engineering, 2020)
: Commercial agriculture is a resource intensive industry that employs significant amounts of agrochemicals to maintain a high yield output. Excessive application of insecticides has detrimental impacts on human health, environment and long-term sustainability. One particular area of interest is in exploring how insects are attracted to specific bands of the visible light spectrum. This paper details the study of several light conditions using Light Emitting Diodes (LEDs) to determine its phototaxis response on the common grasshopper, garden moth and lava beetle. The results conclude that all three insects exhibit positive phototaxis response on wavelengths around 491nm and below, which encompasses ultraviolet, blue and green. The radiant intensity experiment revealed a threshold response of 2.8mW/m2, or 25m in reciprocal distance.